Finishing of flat parts led by lapping kinematics on abrasive disc dressed in agreement with overlap factors - Sanchez, L. E. A. [UNESP]; Jun, N. Z. X. [UNESP]; Fiocchi, A. A. [UNESP] (ASME International, 2009)
This paper discusses the investigation of an abrasive process for finishing flat workpieces, based on the combination of important grinding and lapping characteristics. Instead of loose abrasive grains between the workpiece and the lapping plate, a resinoid grinding wheel of hot-pressed silicon carbide is placed on the plate of a device resembling a lapping machine. The resin bond grinding wheel is dressed with a single-point diamond. In addition to keeping the plate flat, dressing also plays the role of interfering in the behavior of the process by varying the overlap factor (Ud). It was found that the studied process simplify the set-up and can be controlled more easily than in lapping, whose is a painstaking process. The surface roughness and flatness deviation proved comparable to those of lapping, or even finer than it, with the additional advantage of a less contaminated workpiece surface with a shiny appearance. The process was also monitored by acoustic emission (AE), which indicates to be a promissing and suitable technique for use in this process. Copyright © 2008 by ASME.
Keywords: Abrasive process; Flatness deviation; Loose abrasive grains; Resin-bond; Work pieces; Abrasives; Acoustic emission testing; Acoustic emissions; Grinding (comminution); Grinding (machining); Grinding machines; Grinding mills; Grinding wheels; Mechanical engineering; Resins; Silicon carbide; Surface roughness; Lapping